2014
DOI: 10.1021/ic5003176
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Specific Cu(II)-Dependent Peptide Bond Hydrolysis: Similarities and Differences with the Ni(II)-Dependent Reaction

Abstract: Potentiometry and UV-vis and circular dichroism spectroscopies were applied to characterize Cu(II) coordination to the Ac-GASRHWKFL-NH2 peptide. Using HPLC and ESI-MS, we demonstrated that Cu(II) ions cause selective hydrolysis of the Ala-Ser peptide bond in this peptide and characterized the pH and temperature dependence of the reaction. We found that Cu(II)-dependent hydrolysis occurs solely in 4N complexes, in which the equatorial coordination positions of the Cu(II) ion are saturated by peptide donor atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…The ability of the Cu(II) ion to convey the same reactivity was indicated previously [113]. A quantitative study demonstrated that the Cu(II) ion reacted according to the mechanism presented above for Ni(II), but much less eagerly (by one to two orders of magnitude, depending on the temperature) [111].…”
Section: Peptide Bond Hydrolysis In Four-coordinate Square-planar Comsupporting
confidence: 72%
See 1 more Smart Citation
“…The ability of the Cu(II) ion to convey the same reactivity was indicated previously [113]. A quantitative study demonstrated that the Cu(II) ion reacted according to the mechanism presented above for Ni(II), but much less eagerly (by one to two orders of magnitude, depending on the temperature) [111].…”
Section: Peptide Bond Hydrolysis In Four-coordinate Square-planar Comsupporting
confidence: 72%
“…Other recombinant proteins have been purified successfully by this approach in several laboratories, both under native and denaturing conditions [145][146][147]. Fig.…”
Section: Practical Applications Of Metal-assisted Peptide Bond Hydrolmentioning
confidence: 99%
“…There has been reported in the literature that copper ions could induce IgG cleavage [33,34]. Past research had found that when metal ions were present in a specific stereochemistry in the appropriate conformation, metal ions could increase the rate of peptide cleavage and catalyze the reaction [35,36]. In fact, copper ions could bind and enhance the degradation of proteins such as monoclonal antibodies and hydrolyze small peptides and bovine serum albumin, trace amounts of copper ions might be sufficient to enable site-specific, metalmediated monoclonal antibodies degradation [37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in the literature that copper ions could induce IgG cleavage [33,34]. Past research has found that when metal ions with a speci c stereochemistry in the appropriate conformation are present, metal ions can increase the rate of peptide cleavage and catalyse the reaction [35,36]. In fact, copper ions could bind and enhance the degradation of proteins such as monoclonal antibodies and hydrolyse small peptides and bovine serum albumin, and trace amounts of copper ions might be su cient to enable site-speci c, metal-mediated monoclonal antibody degradation [37].…”
Section: Discussionmentioning
confidence: 99%